The Quality of Audit Work Under Expert System - Mohammed, Eman Jasem; Abdullah, Salman Hussein (Journal of Economics and Administrative Sciences, 2022)
The research aims to extrapolate the repercussions of the use of expert systems in the work of the external auditor on the quality of audit, as the research problem was that despite the use of these techniques in audit work, there is a problem related to the efficiency and effectiveness of these technological systems used in audit work, the feasibility of their use and the extent of their impact: The quality of the audit process.The researchers adopted the questionnaire as a tool for collecting study data from a community composed of auditors in auditing offices and companies in Iraq, and the auditors of the Iraqi Federal Financial Supervision Bureau. The number of recovered and valid questionnaires reached (100), or 76% of the total number of questionnaires distributed.The researchers concluded several results, the most important of which was that the auditor in auditing offices and companies in Iraq, in addition to the auditor of supervisory bodies, are aware of the positive effects of using expert systems in the work of the external auditor on the quality of audit work.The researchers also concluded many recommendations, the most important of which are: the need for the regulatory authorities, whether in the public sector represented by regulatory bodies, or audit offices and companies, to benefit from these modern technologies, the need for professionals and audit offices to invest in this modern technology, the need to integrate modern technologies related to the accounting profession And auditing the curricula of Iraqi universities, institutes, and colleges